Toughness improvement of steel X38CrMoV5-1 via alternative manufacturing process and prevention of catastrophic failure in safety parts. (December 2017) - Pastor, A.; Valles, P.; More, W.; Medina, S.F.
Abstract: X38CrMoV5-1 (AISI H11-1) steel parts are often manufactured by die-casting followed by quenching and tempering and the microstructure is highly process-sensitive. In order to eliminate the presence of pores in the parts, a different though more expensive manufacturing process has been implemented, involving the hot rolling of a plate and machining of samples in parallel and perpendicular to the rolling direction. Heat treatment of the samples was optimised and the mechanical tensile properties—yield strength, ultimate strength and ductility—and Charpy toughness were determined for ten samples. The results showed that samples machined in the longitudinal direction gave a toughness of about 20 J, twice the toughness of samples machined in the transverse direction (10 J) and 3.5 times the toughness of cast samples (6 J). Ultimate strength and yield strength were 1580 MPa and 1225 MPa in the transverse direction, 1505 MPa and 1275 MPa in the parallel direction, and 1400 MPa and 1260 MPa as cast, respectively. In the latter case, the standard deviation was much higher due to the presence of pores. Using Griffith's theory, the need for pore-free machined parts to prevent catastrophic failure due to cleavage, especially in lift safety systems, is also demonstrated. Highlights: X38CrMoV5-1 steel showed high hardenability since the microstructure is martensite even for low cooling rates. The die cast parts possess a considerable porosity, 51% of pores ≤ 4 μm and maximum size of around 165 μm in diameter. The largest micropores will cause cleavage fracture at stresses well below the yield strength. To obtain optimum mechanical properties the parts must be machined parallel to the rolling direction of the plate.